A30 DIFFERENCES BETWEEN HUMAN AND MOUSE INTESTINAL EPITHELIAL CELLS IN THEIR INNATE IMMUNE RESPONSES TO BACTERIAL AND HOST STIMULI. (4th March 2021) - Allaire, J M; Poon, A; Crowley, S M; Han, X; Stahl, M; Bressler, B; Jacobson, K; Vallance, B
Abstract: Background: Intestinal epithelial cells (IEC) reside in close contact with the gut microbiota. It is thus important that IEC are hypo-responsive to bacterial products to prevent maladaptive inflammatory responses in the gut, such as those seen in Inflammatory bowel diseases (IBD). This suppression of innate immune signaling in IEC is in part due to their strong expression of Single Ig IL1 related receptor (SIGIRR), a negative regulator of interleukin (IL)-1 and toll-like receptor (TLR) signaling. IL37, a newly recognized anti-inflammatory cytokine has been shown to strongly inhibit innate signaling in cells by binding to, and signaling through SIGIRR, leading to suppression of various forms of inflammation in mice. Few studies have looked at the function of IL-37/SIGIRR in IEC and their potential use to balance inflammatory responses. Notably, while many groups have studied IEC immune response in vitro, using transformed IEC lines, our focus is on primary-derived IEC which more accurately reflect in vivo responses. Aims: To characterize IEC intrinsic and species-specific immune responses elicited by bacteria and host products as well as the role of IL37/SIGIRR in regulating this innate signaling. Methods: We used organoid to study the innate immune responses of primary IEC derived from human or mouse colon (colonoids). After stimulation with inflammatory stimuli (IL1β, FliC and LPS), qPCR, ELISA, Milliplex Multiplex Assay and Western blot were used to determine modification in signalling pathway and cytokine/chemokine secretion. Results: Using colonoids derived from healthy donors, we demonstrated that unlike transformed cell lines or mouse IEC, human IEC respond only to the bacterial product FliC, and not to LPS or IL1β. We further characterized human colonoid innate immune responses and despite significant inter-individual variability upon FliC stimulation, all organoids released several chemokines (IL8, CXCL1, CXCL2, CCL2 and CCL20). We showed for the first time that IL37 attenuated these innate immune responses through inhibition of intracellular signaling pathways (p38 and NFkB). Using colonoids derived from wildtype and Sigirr deficient mice, we found that mice IEC were responsive to IL1b and FliC and that the suppressive effects of IL37 were Sigirr dependent. Conclusions: Our results show that human IEC show variability among individuals in the magnitude of their innate immune responses, and these responses differ from those obtained from transformed cells and primary mouse IEC. For the first time, we show that IL37 suppresses IEC innate immune responses, through its ability to signal through Sigirr. Further investigations will assess the ability of IL37 to control inflammation of IEC derived from IBD patients, as a potential therapeutic to promote gut health. Funding Agencies: CAG, CIHRMSFHR